Synthesis and Characterization of a New 2-{(E)-[(4-aminophenyl)imino]methyl}-6-bromo-4-chlorophenol and Its Complexes with Co (II), Ni (II), Cu (II), and Zn (II): An Experimental and DFT Study - Bakirdere, Emine Gulhan; Fellah, Mehmet Ferdi; Canpolat, Erdal; Kaya, Mehmet (Taylor & Francis Inc, 2015)
The complexes of Co, Ni, Cu and Zn with 2-{(E)-[(4-aminophenyl)imino]methyl}-6-bromo-4-chlorophenol were prepared and characterized by physical, spectral, and analytical data. The metal:ligand stoichiometric ratio is 1:2 in all the complexes produced. The bidentate behavior of the ligand was accomplished via the phenolic oxygen and the azomethine nitrogen atoms. Suitable structures have been proposed for the complexes synthesized. The theoretically optimized geometries of complexes have tetrahedral structures. The stretching frequencies of CN, CO, and NH were computed to be in good agreement with experimental data. All calculated frequencies fall within 2% of the experimental frequency regions.
Keywords: Schiff base; transition metal complex; DFT